Navigating the Digital Frontier: An In-depth Analysis of Classroom Digitalization - Suyash Dhumal; Krish Devrukhkar (International Journal of Electrical and Communication Engineering Technology, 2024)
When we talk about the Internet, we think about the likes of social media, or platforms like Google which has an unfathomable archive of information which is available for any and every individual to use up to their own likings. However, there are several challenges and complexities associated with the Internet's impact on social interactions. The issues of online harassment, privacy, and the addictive nature of social media have become prominent concerns. Our online and offline lives are becoming more and more entwined, which begs the concerns of how real our online personas are and how emotionally taxing constant connectedness may be. However, there are several challenges and complexities associated with the Internet's impact on social interactions. The issues of online harassment, privacy, and the addictive nature of social media have become prominent concerns. Our online and offline lives are becoming more and more entwined, which begs the concerns of how real our online personas are and how emotionally taxing constant contact is. The things which also cross our minds are that the Internet is a necessity across the world and that the people cannot live without the Internet in the modern age of mankind. Now, while it is such a behemoth of a communications and lifestyle tool, there are discrete opinions about it as well.
Keywords: Digitalization; E-learning; Internet of things (IoT); Navigation; education System